PERAN AKUNTANSI DALAM MENGELOLA RISIKO VALUTA ASING: TANTANGAN DAN SOLUSI DI PASAR GLOBAL - Ihsan, Khairil; Andini, Nisha; Hairani, Hairani (Journal of Management, Economic and Accounting (JMEA), 2025)
In an era of intensifying globalization, companies worldwide operate in an increasingly complex and dynamic business environment. Tighter global economic integration has encouraged companies to conduct cross-border transactions, thus involving various foreign currencies. This is inevitable considering the increasingly complex global supply chain, increasing business competition, and the need to expand markets. This type of research is a qualitative descriptive study that focuses on available sources of information about the power of data analysis. These sources come from various books and publications that discuss existing theories clearly and comprehensively to create text in the form of articles. Risk management is an essential strategic instrument in identifying, measuring, and mitigating uncertainty to achieve organizational goals and increase stakeholder trust. In a global market ecosystem influenced by the flow of globalization and regulatory complexity, understanding foreign exchange is very crucial because of its function as an international payment instrument and investment instrument that maintains economic stability. The low public compliance is triggered by various multidimensional factors, ranging from minimal awareness and knowledge of taxation, fluctuations in economic income, to the absence of strict legal sanctions for violators. As a solution, the village authorities are taking an approach through optimizing public services and persuasive outreach to provide education regarding the rights and obligations of citizens, which ultimately aims to restore the stability of regional tax revenues.